(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Bradinothrips musae (Hood), a new thrip for European fauna, is recorded. It has been collected in a greenhouse near Bergamo (Lombardy) on Spathiphyllum sp. coming from Costa Rica.